The Influence of Character Education and Family in Preparing Future Leaders Through Christian Education and P5 Practices - Satyo Istandar Tan, Paulus (Universitas Pendidikan Ganesha, 2025)
This study addresses the challenges in fostering ethical leadership in the next generation. In a rapidly developing world, it is imperative to integrate character education, Christian education, family involvement, and the practice of Pancasila values ​​(P5) to form competent and morally responsible leaders. This study aims to identify the influence of these factors on leadership development, using a survey for data collection and Partial Least Squares (PLS) structural model analysis. This study usesquantitative approach with quasi-experimental research design. The population in this study were junior and senior high school students of Christian schools. Data were collected through several instruments, including Questionnaires, Observations, Interviews.Data were analyzed using Normality and Homogeneity Test, T-test and Simple Regression Analysis.The results show that character and Christian education have a significant impact on the formation of future leaders. The implications of this study are designing a systematic character learning program and involving families as active partners. In addition, P5 practices can be used as a bridge to contextualize faith values ​​in students' real lives, thereby strengthening the profile of leadership with integrity and based on Christian faith and Pancasila values.